2016
DOI: 10.1536/ihj.15-389
|View full text |Cite
|
Sign up to set email alerts
|

Biological Antioxidant Potential Negatively Correlates With Carotid Artery Intima-Media Thickness

Abstract: SummaryOxidative stress is a crucial factor in the pathogenesis and development of cardiovascular disease. Recently, simplified methods for the detection of reactive oxygen species (ROS) using the derivatives of reactive oxygen metabolites (dROMs) test as an index of ROS products and the biological antioxidant potential (BAP) test as an index of antioxidant potential have been utilized. These methods are easy to perform, quick, inexpensive since they use small equipment, and provide reliable results compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Interestingly, in a recent paper, Yagi and colleagues [ 55 ] demonstrated that BAP was strongly correlated with carotid artery IMT suggesting that it may be considered a suitable risk marker for carotid atherosclerosis; moreover, they postulate that the measurements of BAP may be superior to the measurements of glutathione peroxidase, superoxide dismutase, catalase, and total antioxidant status for the assessment of antioxidant potential. Our results emphasize that the first detectable event of a redox disturbance is the repairing intervention of the antioxidant barrier that is thus decreased as overutilized.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a recent paper, Yagi and colleagues [ 55 ] demonstrated that BAP was strongly correlated with carotid artery IMT suggesting that it may be considered a suitable risk marker for carotid atherosclerosis; moreover, they postulate that the measurements of BAP may be superior to the measurements of glutathione peroxidase, superoxide dismutase, catalase, and total antioxidant status for the assessment of antioxidant potential. Our results emphasize that the first detectable event of a redox disturbance is the repairing intervention of the antioxidant barrier that is thus decreased as overutilized.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study, the IMT was correlated with d-ROMs in a population with hypercholesterolemia [ 28 ]. In the second study, the IMT was not correlated with d-ROMs in healthy people and those with mild disease conditions [ 29 ]. This discrepancy was likely to attributable to the differences in subject backgrounds and age.…”
Section: Commentsmentioning
confidence: 99%
“…The thickness of the carotid artery walls was measured on straight longitudinal 10 mm segments of the common carotid artery at positions 2-3 cm apart from the carotid bulb. 6,16) The thickness was evaluated in arterial segments free of plaques and was defined as the distance between the leading edge of the most internal echogenic line (lumen-intima interface) and the second echogenic line (media-adventitia interface). Measurement of body fluid volume: Multi-frequency segmental bioelectrical impedance was measured by using the InBody 720.…”
Section: Subjects and Biochemical Analysismentioning
confidence: 99%